Sequelae Following Acute Encephalitis Syndrome Caused by Orientia Tsutsugamushi. Issue 5 (May 2020) - Prakash Gangwar, Surya; Thangaraj, Jeromie Wesley Vivian; Zaman, Kamran; Vairamani, Vignesh; Mittal, Mahima; Murhekar, Manoj
Abstract : We evaluated 146 patients with acute encephalitis syndrome caused by Orientia tsutsugamushi, after median interval of 5 months of hospitalization, to estimate the proportion and spectrum of disability. Fifty-six (38.4%) had mild, whereas 19 (13%) had moderate to severe degree of disability. Most patients had impairment in the domain of cognition and behavior. Abstract : Supplemental Digital Content is available in the text.